Proton disorder in a short intramolecular hydrogen bond investigated by single‐crystal neutron diffraction at 2.5 and 170 K. Issue 12 (13th November 2018) - Truong, Khai-Nghi; Meven, Martin; Englert, Ulli
Abstract : Single‐crystal neutron diffraction at 2.5 K and a subset of neutron data collected at 170 K, combined with information from X‐ray diffraction at the same temperature, suggest static disorder for the proton in the short intramolecular hydrogen bond of 3‐[2‐(pyridin‐4‐yl)ethyl]pentane‐2, 4‐dione. Abstract : The substituted acetylacetone 3‐[2‐(pyridin‐4‐yl)ethyl]pentane‐2, 4‐dione, C12 H15 NO2, (1), with an ethylene bridge between the acetylacetone moiety and the heteroaromatic ring, represents an attractive linker for mixed‐metal coordination polymers. In the crystal, (1) adopts an antiperiplanar conformation with respect to the C—C bond in the central ethylene group and almost coplanar acetylacetone and pyridyl groups. The ditopic molecule exists as the enol tautomer, with proton disorder in the short intramolecular hydrogen bond. Single‐crystal neutron diffraction at 2.5 K indicated site occupancies of 0.602 (17) and 0.398 (17). The geometry of the acetylacetone moiety is in agreement with such a site preference of the bridging hydrogen: the O atom associated with the preferred H‐atom site subtends the longer [1.305 (2) Å] and the more carbonyl‐like O atom the shorter [1.288 (2) Å] C—O bond. Based on structure‐factor calculations for the alternative H‐atom sites, reflections particularly sensitive for proton distribution were identified and measured in a second neutron data collection at 170 K. At this temperature, 546 independent neutron intensities were used to refine positional and isotropic displacement parameters for a structure model in which parameters for C and O atoms were constrained to those obtained by single‐crystal X‐ray diffraction at the same temperature. The site occupancies for the disordered proton do not significantly differ from those at 2.5 K.